Visualization of medical images using VTK (Report) - Zubir, Nazira; Mat Noor, Nina Azurainie; Pushpanathan, Kalananthni (2016)
The primary objective of the imaging assignment is to visual medical images using the Visualization Toolkit (VTK). An unknown group of image database was provided to unravel the precise organs or tissues and any abnormalities that may presence. VTK is a software system for 3D computer graphics for the usage of modelling, image processing, volume rendering, scientific visualization, and information visualization. VTK is executed as a C++ toolkit. It requires users to build applications by combining various objects into an application. VTK employs Kitware’s Quality Software Process (CMake, CTest, CDash, and CPack). Hence, it enables the application to produce robust and high-quality code. The usage of VTK is extended to commercial applications apart from research and development. It serves as the foundation for various advanced visualization applications for example ParaView, VisIt, VisTrails, Slicer, MayaVi, and OsiriX.